Three-dimensional waves of excitation during Dictyostelium morphogenesis. - Steinbock, O (1993)
Cells in Dictyostelium slugs follow well-defined patterns of motion. We found that the chemotactic cell response is controlled by a scroll wave of messenger concentration in the highly excitable prestalk zone of the slug that decays in the less-excitable prespore region into planar wave fronts. This phenomenon is investigated by numerical solutions of partial differential equations that couple local nonlinear kinetics and diffusive transport of the chemotactic signal. In the interface of both regions a complex twisted scroll wave is formed that reduces the wave frequency in the prespore zone. The spatio-temporal dynamics of waves and filaments are followed over 33 periods of rotation. These results yield an explanation of collective self-organized cell motion in a multicellular organism.